PICTIONARY GAME: ITS EFFECT TO UPGRADE ESP STUDENTS' VOCABULARY MASTERY AT SMK NEGERI 2 PANGKEP - Rifdah Qurratul Ain; Aulia Ramanda Nawir; Andi Muh. Utama Putra; Ardiana Ardiana; Suwarni Suwarni (STKIP Siliwangi, 2023)
Games have been proven to be a classic yet effective technique in teaching English vocabulary. In the English for Specific Purposes (ESP) Classroom, games can be employed to introduce both common and specific words enjoyably. This study aims to increase the vocabulary mastery of ESP students by using Pictionary Game in the Fashion study program at SMK Negeri 2 Pangkep. The research method applied in this research is qualitative: Classroom Action Research (CAR). Conducted in SMK Negeri 2 Pangkep in the academic year 2021/2022, this research involved 26 second-grade Fashion students as the sample. The treatment consisted of two cycles with three meetings each cycle. To collect the data, tests were used. The results showed that the implementation of the Pictionary game technique improved students' vocabulary achievement. It can be seen from the results of students’ scores which improved in the post-tests. This implies that the Pictionary game technique helps students to learn vocabulary more easily.